2015
DOI: 10.1017/s0033291715001063
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cocaine consumption are associated with fluctuations in self-reported impulsivity and gambling decision-making

Abstract: Background. In cross-sectional studies, cocaine users generally display elevated levels of selfreported and cognitive impulsivity. To what extent these impairments are stable v. variable markers of cocaine use disorder, and, thus, are pre-existing or drug-induced, has not yet been systematically investigated. Method. We conducted a longitudinal study with cocaine users who changed or maintained their consumption intensity, measuring self-reported impulsivity with the Barratt Impulsiveness Scale (BIS-11), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 65 publications
6
49
2
1
Order By: Relevance
“…This view is consistent with reports that recent stimulant use may attenuate pre-existing cognitive deficits (1417), while nonetheless contributing to increased cognitive dysfunction with chronic use (5, 30, 31). Similarly, given that chronic stimulant use appears to exacerbate impulsivity (20), reductions in impulsivity associated with recent use are likely to be temporary and counterproductive in the long-term. Since BIS-11 scores predict poor treatment response in methamphetamine users (10), the current findings suggest that increases in impulsivity in early abstinence may also contribute to treatment non-response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is consistent with reports that recent stimulant use may attenuate pre-existing cognitive deficits (1417), while nonetheless contributing to increased cognitive dysfunction with chronic use (5, 30, 31). Similarly, given that chronic stimulant use appears to exacerbate impulsivity (20), reductions in impulsivity associated with recent use are likely to be temporary and counterproductive in the long-term. Since BIS-11 scores predict poor treatment response in methamphetamine users (10), the current findings suggest that increases in impulsivity in early abstinence may also contribute to treatment non-response.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of methamphetamine-dependent participants abstinent for various durations, subjects who were abstinent for 30 days reported non-significantly higher scores on the BIS-11 than those who were abstinent for 6 days, possibly suggesting a subtle reduction in impulsivity from recent use (19). On the other hand, a longitudinal study of cocaine users showed that those who decreased their cocaine use over one year tended to report decreased impulsivity on the BIS-11, while those who increased their use tended to report increased impulsivity (20). These longitudinal results are contrary to the aforementioned literature, and may reflect differences in the acute versus chronic effects of stimulant use on impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that delay discounting predicted abstinence from cocaine across conditions of an experimental manipulation (a contingency management monetary voucher system for negative urines) (Washio et al, 2011). However, changes in cocaine use over a year did not necessarily correspond with differences in delay discounting (Hulka et al, 2015). Thus, delay discounting may be sufficient, though not necessary, to predict future cocaine use in clinical settings.…”
Section: Choice Procedures Suitable For Treatment-seekersmentioning
confidence: 99%
“…On one hand, there is empirical support for impulsivity being a stable trait that predicts the onset and progression of drug use (Doran and Trim; Audrain-McGovern et al 2009; Settles et al 2010; Moffitt et al 2011; Odum 2011; Quinn and Harden 2013; Fernie et al 2013). On the other hand, there is also ample evidence that repeated use of drugs makes individuals more impulsive (Elkins et al 2006; Simon et al 2007; Mendez et al 2010; Quinn et al 2011; Quinn and Harden 2013), a change that typically returns to normal after recovery (Yi et al 2008; Bankston et al 2009; Blonigen et al 2013; Cicolini et al 2014; Littlefield et al 2015; Hulka et al 2015). Thus, impulsivity can both pre-date and result from the drug use, serving as both a cause and consequence, and making it difficult to interpret cross-sectional studies of impulsivity in individuals with addictive disorders.…”
Section: Introductionmentioning
confidence: 99%